Visible light photodegradation of azo dye by Cu/TiO2 - Riaz, N. (Trans Tech Publications Ltd, 2014)
Cu/TiO2 photocatalysts with different metal loading were prepared via modified deposition-precipitation method with the intention to reduce the band gap for Orange II degradation and mineralization under visible light radiation. The photocatalysts were characterized using thermal gravimetric analysis, powder X-ray diffraction, diffuse reflectance UV-Visible spectroscopy and field-emission scanning electron microscopy. 10 wt photocatalysts showed the best performance compared to the bare TiO2. Â© (2014) Trans Tech Publications, Switzerland.